2010
DOI: 10.1242/jeb.043455
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial metabolism of Pacific bluefin tuna (Thunnus orientalis)

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…specific dynamic action (SDA)] (Jobling, 1981;Secor, 2009;Clark et al, 2010). However, the exact time will vary across species and temperatures, with cold-water species typically having longer SDA (Secor, 2009).…”
Section: Minimum Oxygen Consumption Ratementioning
confidence: 99%
“…specific dynamic action (SDA)] (Jobling, 1981;Secor, 2009;Clark et al, 2010). However, the exact time will vary across species and temperatures, with cold-water species typically having longer SDA (Secor, 2009).…”
Section: Minimum Oxygen Consumption Ratementioning
confidence: 99%
“…Bluefin tuna display the highest level of endothermy among teleost fishes, using metabolic heat to maintain their body temperature above the ambient water temperature (Carey and Gibson, 1983;Block et al, 2001;Walli et al, 2009). They also exhibit a high metabolic capacity and rates of digestion relative to other fishes (Brill, 1996;Blank et al, 2007;Clark et al, 2010). Bluefin tuna experience a wide range of ambient temperatures in the ocean and are often exposed to large changes in ambient temperature (~10°C) through their horizontal and vertical movements (Gunn and Block, 2001;Walli et al, 2009;Kitagawa et al, 2007b;Boustany et al, 2010;Lawson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The well-observed postprandial increase in metabolism is also termed the heat increment of feeding (HIF) or diet-induced thermogenesis (DIT). In bluefin tuna, metabolic rate and visceral temperature have both been found to increase on ingestion of a meal (Carey et al, 1984;Fitzgibbon and Seymour, 2009;Clark et al, 2010). Direct measurements of oxygen consumption rates in a flume have shown that postprandial changes in visceral temperature closely track changes in metabolic rate, with a small lag (Clark et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge there is no study describing the transcriptional changes during and following a postprandial period in fish, with most studies focusing on the changes in metabolic rate (Clark et al, 2010;Vanella et al, 2010) and the plasma level of metabolites following feeding (Eames et al, 2010;Eliason et al, 2010;Wood et al, 2010). We have investigated transcriptional regulation in the fast myotomal muscle of male zebrafish in response to a single satiating meal delivered at first light.…”
Section: Introductionmentioning
confidence: 99%